PENGARUH VARIASI MEDIA PENDINGIN OLI, DROMUS, MINYAK SAYUR TERHADAP KEKASARAN PERMUKAAN BAJA SS-400 PADA PROSES MESIN BUBUT KONVENSIONAL (LATHE MACHINE) - Saputra, Antoni; ., Firdaus; Gunawan, Indra (MACHINERY Jurnal Teknologi Terapan, 2021)
The development of increasingly sophisticated and modern technology, especially in the industrial field, both machine tools, power plants and metallurgy play an important role in the industrial world. As is the case for machine tools used in the machining process, including lathes, milling machines, drilling machines, scrap machines, grinding, and others. The lathe process is the process of forming a material by removing some of the material in the form of a snarl due to the relative motion of the tool to the workpiece, where the workpiece is rotated on the spindle and the chisel is delivered to the workpiece in a translational manner. The quality of the turning results, especially on the surface, is strongly influenced by three parameters, namely spindle speed (Speed), feed motion (feed), and depth of cut (Depth of Cut). As for other factors that support the quality of the turning results, including the workpiece, the type of chisel used and the cooling media actually have a significant influence, the cooling medium used is Oil, Dromus and Vegetable Oil, the chisel used by HSS and the depth of cutting (F) 0.1 mm and 0.2 mm. The percentage of the effect of variations in cooling media on the surface roughness of SS-400 steel in the turning process is as follows: Oil = 75% Dromus = 64% Vegetable Oil = 70% It can be seen from the above percentage that for now the cooling medium Oil is the most influential cooling medium. And better than Dromus and Vegetable Oil cooling media against roughness in the turning process.